Mirror, mirror on the wall, wish that I could rent it all : a case study on consumer adoption to fashion-rental services on the Swedish market - Norr, Ylva; Ondiege, Gabriella (SLU/Dept. of Economics, 2020)
Although raised awareness of how excess consumption of fashion causes great environmental concern in society, changes in consumption patterns have been modest. It is therefore questionable whether reduced consumption is likely to happen, it might be better to envision equally compelling ways to address consumers’ desire for fashion. The phenomenon of fashion-rental services seems promising to encourage resource efficiency in production and consumption of fashion. However, it necessitates changes in consumption practices. Previous research lacks deeper insights about consumers’ participation and engagement in offerings that build on access to products in the context of fashion. Therefore, the aim of this study is to investigate and critically reflect on conditions that influence consumer adoption to fashion-rental services on the Swedish market. New approaches to the topic of consumer adoption to fashion-rental services have been taken, such as following a case study research strategy, where semi-structured interviews have been conducted with market experts within the area of fashion. Moreover, using the Consumer Culture Theory as the analytical perspective. This study shows that the conditions of experiment with style, identity and belonging, trend of services as well as changes in daily life and environmental values are perceived as drivers for consumer adoption to fashion-rental services on the Swedish market. It further shows that the conditions of emotional attachment, the “kick” of material things, ease of use, ownership, consumer mindset, and supply on the market are perceived to hinder consumer adoption to fashion-rental services on the Swedish market. The findings indicate that how fashion consumption is perceived by Swedish consumers determines whether a fashion-rental service is adopted and thereby diffused on the Swedish market. These findings further reflect the challenges of combining fashion consumption and sustainable development.